Alfred Marshall's Last Challenge His Book on Economic Progress. - Caldari, Katia (Cambridge Scholars Publisher, 2020)
This text presents Alfred Marshall's final, unfinished, and unpublished book. His main volume, Principles of Economics, was first published in 1890, and was, for a long period of time, the textbook par excellence on which generations of economists were trained. Despite its success and its importance, the book, in its eight editions, testifies to some extent to the failure of Marshall's original editorial project which should have consisted of multiple volumes and culminated with the publication of a final work on economic progress. Marshall's death in 1924 made it impossible to realize his pro.